Pembangunan Sistem Enterprise Resource Planning pada Griya Laundry - Rahmat Al Aziz; Faizatul Amalia; Adam Hendra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Information technology is growing in this era makes things become faster. In this research, the researcher tries to model and apply business process using ERP program as the foundation in ERP system development at Griya Laundry Company. In this research is the business process used by the company and modeled in the form of Business Process & Notation. Implementation of software using web programming language. The use of HTML, PHP, CI Framework, JQuery, and CSS as the foundation of the application builder programming. Based on the test results obtained, GLErp system can be accepted by. Preferably in terms of benefits, satisfaction, use in use, and ease of learning with percentage of 68,20%. Based on the results of the validation tests obtained, the GLErp application has fulfilled all the needs.